Daddy - Steel, Danielle (London Corgi books, 1989)
The divorce of Oliver and Sarah after eighteen years of marriage becomes the catalyst that compels three generations to explore their lives, loves, goals, and expectations.
Keywords: Fathers -- Fathers and sons -- Life change events